2021
DOI: 10.3390/antiox10020240
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Alkaline Phosphatase Combined with Voluntary Physical Activity Alleviates Experimental Colitis in Obese Mice. Involvement of Oxidative Stress, Myokines, Adipokines and Proinflammatory Biomarkers

Abstract: Intestinal alkaline phosphatase (IAP) is an essential mucosal defense factor involved in the process of maintenance of gut homeostasis. We determined the effect of moderate exercise (voluntary wheel running) with or without treatment with IAP on the course of experimental murine 2,4,6-trinitrobenzenesulfonic acid (TNBS) colitis by assessing disease activity index (DAI), colonic blood flow (CBF), plasma myokine irisin levels and the colonic and adipose tissue expression of proinflammatory cytokines, markers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…We have confirmed our previous observation [ 36 ] that the combination of voluntary physical activity, along with IAP administration, improved DAI as compared with mice accessing SW only, or those administered with IAP alone against colitis, as reflected by gross macroscopic and microscopic assessments. This marked improvement in colitis was manifested by a reduction in mucosal bleeding and hemorrhagic lesions, less inflammatory reaction, white blood cells’ mucosal infiltration and greater signs of regeneration of damaged colonic mucosa.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We have confirmed our previous observation [ 36 ] that the combination of voluntary physical activity, along with IAP administration, improved DAI as compared with mice accessing SW only, or those administered with IAP alone against colitis, as reflected by gross macroscopic and microscopic assessments. This marked improvement in colitis was manifested by a reduction in mucosal bleeding and hemorrhagic lesions, less inflammatory reaction, white blood cells’ mucosal infiltration and greater signs of regeneration of damaged colonic mucosa.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the IAP-KO mice are characterized by dysbiosis but the administration of exogenous IAP reversed this dysbiosis when compared to wild type mice [ 35 ]. Recently, we have reported that voluntary exercise and IAP exerted a beneficial protective effect against inflammatory intestinal changes [ 36 ]; however, the alterations in microbiota at the phylum and genus levels, oxidative stress biomarkers, protein expression of proinflammatory factors as well as skeletal muscle strength changes in obesity-induced exacerbation of colitis have not been studied before. Therefore, our present study was designed to evaluate the effect of IAP administration, combined or not with moderate physical activity, on experimental colitis, with a major focus addressed to changes in intestinal microbiota, since microbiota alterations have been associated with the development of intestinal inflammation in experimental murine models of colitis [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity and metabolic disorders are accompanied by chronic low-grade inflammation. Inflammatory cytokines in adipose tissue induced by obesity, such as TNF-α, IL-1β, and IL-6, increased [ 29 , 30 , 31 ]. In addition, adipose tissue macrophages in obese mice showed more pro-inflammatory phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…IAP also has an indirect role in maintaining barrier function by inhibiting proinflammatory molecules such as LPS and cytokines including tumor necrosis factor-alpha (TNF-α) and IL-1β, which disrupt barrier function. Danielak et al showed that supplementation of IAP in combination with voluntary exercise caused a reduced expression of proinflammatory cytokines TNF-α, IL-1 β, and IL-6 in a colitis mouse model fed with standard diet (SD) or high-fat diet (HFD) [ 27 ]. In another study, oral IAP reduced TNF-α and IL-6 in brains of mice mode of heart failure [ 22 ].…”
Section: Iap Inflammation and Tlr4mentioning
confidence: 99%